ETIKA BISNIS MEMODERASI PENGARUH MANAJEMEN RISIKO, MODAL INTELEKTUAL HIJAU DAN HAK PEMEGANG SAHAM TERHADAP KEUANGAN BERKELANJUTAN - Lusmeida, Herlina; Khomsiyah; J. Arsjah, Regina (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
By using business ethics as a moderator, this research seeks to examine the impact of management risk, environmentally friendly intellectual capital, and shareholder rights on sustainable financing. This research uses secondary data, with the research period starting from 2018 to 2021, multiple linear regression analysis is used to analyze the data. The research sample consisted of 65 financial services organizations listed on the Indonesia Stock Exchange. Sustainable finance can be influenced by risk management, green intellectual capital and ethical corporate practices. Meanwhile, shareholder rights have no effect on sustainable finance. The research results show that business ethics does not strengthen the positive influence of risk management, green intellectual capital on sustainable finance, but there is an interaction between business ethics and shareholder rights so that it can influence sustainable finance.